2011
DOI: 10.1186/1756-0500-4-315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlation of nonalcoholic fatty liver disease in a Chinese taxi drivers population in Taiwan: Experience at a teaching hospital

Abstract: BackgroundTo explore any gender-related differences in the prevalence of conditions-associated with non-alcoholic fatty liver disease (NAFLD) among Taiwanese taxi drivers in Taipei, Taiwan.MethodsWe studied 1635 healthy taxi drivers (1541 males and 94 females) who volunteered for physical check-ups in 2006. Blood samples and ultrasound fatty liver sonography results were collected.ResultsThe prevalence of NAFLD was 66.4% and revealed no statistically significant decrease with increasing age (p = 0.58). Males e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 29 publications
2
28
2
1
Order By: Relevance
“…However, it was interesting that that elderly female gender represented significant risk factors related to the likelihood of a NAFLD. Such a finding would appear to be inconsistent with the results of other studies for general population or occupational population conducted elsewhere [3,4,[7][8][9]11,12]. The proportion of obesity in males was higher than females among aged <50 yrs but the prevalence of an obesity for males proved to be substantially greater than it was for females among 60 years or above [21].…”
Section: Discussion Prevalence and Cardiovascular Factors For The Devcontrasting
confidence: 56%
See 3 more Smart Citations
“…However, it was interesting that that elderly female gender represented significant risk factors related to the likelihood of a NAFLD. Such a finding would appear to be inconsistent with the results of other studies for general population or occupational population conducted elsewhere [3,4,[7][8][9]11,12]. The proportion of obesity in males was higher than females among aged <50 yrs but the prevalence of an obesity for males proved to be substantially greater than it was for females among 60 years or above [21].…”
Section: Discussion Prevalence and Cardiovascular Factors For The Devcontrasting
confidence: 56%
“…This disparity would likely be largely due to differences between different population stocks in addition to differences in the specifics of diagnostic criteria for such a NAFLD. This is one of the possible reasons that the prevalence of NAFLD in this elderly agricultural and fishing population (27.2%) was lower than the corresponding figure presented in a previous occupational population-based study conducted in Chinese populations [4,9,12]. Our study demonstrated NAFLD to be a disease of elderly age group with a mean age at presentation being 67 years.…”
Section: Discussion Prevalence and Cardiovascular Factors For The Devcontrasting
confidence: 48%
See 2 more Smart Citations
“…In Hong Kong, a community based study employing state of the art proton magnetic reso nance spectroscopy to quantify liver fat estimated a NAFLD prevalence of 28.8%: 19.3% in individuals who were not obese and 60.5% among those who were obese 49 . Similarly, in Taiwan, the preva lence of NAFLD was reported to be 11.4% in the general community 50 but higher in certain sub populations, including the elderly (mean age 70.3 ± 4.6 years, 50.1% prevalence) 51 52 .…”
Section: Incidence Of Nafld and Future Projections In Europementioning
confidence: 91%